2017
DOI: 10.5851/kosfa.2017.37.5.716
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical Characteristics in Relation to Meat Quality Traits of Eight Major Muscles from Hanwoo Steers

Abstract: The objective of this study was to determine the relationship between composition of muscle fiber types and meat quality traits of eight major muscles from Hanwoo steers. Longissimus lumborum (LL), psoas major (PM), semimembranosus (SM), semitendinosus (ST), gluteus medius (GM), triceps brachii (TB), rectus abdominis (RA) and superficialis flexor (SF) muscles were obtained from 9 Hanwoo steers and subjected to histochemical analysis. There were significant (p<0.05) differences in fiber number percentage (FNP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 41 publications
6
13
0
Order By: Relevance
“…As expected, the diameter of myofibers in LL and SM muscles were significantly longer than PM muscle (p<0.05). This finding is in line with Joo et al [ 4 ], who also observed smaller myofiber diameter in PM muscle than LL and SM muscles. There was no difference between LL and SM muscle for the myofiber diameter, irrespective of cattle breeds.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…As expected, the diameter of myofibers in LL and SM muscles were significantly longer than PM muscle (p<0.05). This finding is in line with Joo et al [ 4 ], who also observed smaller myofiber diameter in PM muscle than LL and SM muscles. There was no difference between LL and SM muscle for the myofiber diameter, irrespective of cattle breeds.…”
Section: Resultssupporting
confidence: 93%
“…There was a significant interaction effect of breed×muscle for cooking loss (p<0.05). SM muscle showed the highest cooking loss compared to LL and PM muscles ( Table 5 ), which is in accordance with the results of Joo et al [ 4 ].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…FNP refers to the ratio of counted fiber number of each fiber type to the total counted fiber number. FAP was the ratio of total cross-sectional area of each fiber type to total fiber area (Hwang, Joo, Bakhsh, Ismail, & Joo, 2017;Joo, Lee, Hwang, & Joo, 2017).…”
Section: Histochemical Analysismentioning
confidence: 99%